Effect of selective β-blockers on spirometry in a 4 hour bronchial provocation test in patients with bronchoobstructive pathology - K. A. Zykov; O. Y. Agapova; B. M. Nazarov; Y. A. Dolgusheva; L. G. Ratova; I. E. Chazova (Медицинский совет, 2014)
Administration of β-blockers in patients with cardiovascular pathology combined with obstructive bronchial or pulmonary disease (bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD)) is associated with a risk of bronchospasm in a number of patients. No test has been developed so far to identify such patients. We recommend to carry out a 4-hour bronchial provocation test with a small dose of beta 1 selective β-blocker bisoprolol. The study included 31 patients with BA and COPD with concomitant cardiovascular disease requiring administration of β-blockers. Results of six consecutive spirometry tests, which continued for 4 hours to assess the effect of bisoprolol on airway function, are demonstrated. The maximum reduction in FEV1 after administration of the β-blocker was identified. Spirometry test results were compared in patients with BA and COPD.